The Influence of Self-esteem, Self-efficacy, And Optimism on MSMEs Business Resilience in Pasar Jaya Pasar Rumput - Syafira, Sania; Mulyanti, Rita Yuni; Abdulah, Budiman (International Journal of Entrepreneurship and Sustainability Studies, 2025)
This research analyzes the impact of self-esteem, self-efficacy, and optimism on business resilience among Micro, Small, and Medium Enterprises (MSMEs) in Pasar Jaya Pasar Rumput. The selected site represents a vulnerable urban business environment affected by redevelopment projects, making it a relevant context for exploring the dynamics of entrepreneurship and sustainable development. Employing a quantitative research design, data were collected from 185 respondents who manage MSMEs in Pasar Jaya Pasar Rumput through a questionnaire. Analysis was carried out using SEM with SmartPLS software. The results obtained from this research show that self-esteem, self-efficacy, and optimism have a positive and significant effect on business resilience in MSMEs in Pasar Jaya Pasar Rumput. The results support the Resource-Based View (RBV) theory. This research offers a novel contribution by integrating psychological capital into the discourse of entrepreneurial resilience within the broader sustainability framework. The practical implications suggest the need for empowerment programs that include psychological development to strengthen long-term business sustainability. Policymakers are encouraged to incorporate psychological resource training into MSME support strategies to promote resilience and inclusive economic growth in uncertain urban environments